Kinematik Forward dan Analisis Kesalahan Pada Kesejajaran Sumbu Join Mekanisme Paralel Rotasi Murni 3-URU - Syamsul Huda; Ilham Fahmi; Mulyadi Bur (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
In this paper we discussed the forward kinematic and constrain error of 3-URU parallel mechanism. The mechanism was composed of URU kinematic chain consisting of three parallel joint axes and two intersecting joint axes. The direction of parallel joint axis representing direction of force constraints acting on center of platform rotation. In this research was investigated the effect of error of direction of parallel joint exes on kinematic chains to the platform orientation and position of center of platform rotation.  It is also developed the formulation of forward kinematic of the mechanism. The forward kinematic was carried out by taking account geometric constraint of platform motion which is derived analytically by using software Maple 16. On the other hand, the constraint error was evaluated using the CAD simulation Autodesk Inventor. Based on the result, it can be summarized that error of parallel joint axes produced significant effect on error of platform motion especially for location of the center of platform rotation which is classified as uncompensated error. The formulation of forward kinematic was successfully derived which is confirmed with inverse kinematic and CAD simulation.